The garden asparagus (Asparagus officinalis L.) mitochondrial genome revealed rich sequence variation throughout whole sequencing data - Sheng, Wentao; Deng, Jianlan; Wang, Chao; Kuang, Quan (Frontiers in Plant Science, 2023)
Garden asparagus (Asparagus officinalis L.) is a horticultural crop with high nutritional and medical value, considered an ideal plant for sex determination research among many dioecious plants, whose genomic information can support genetic analysis and breeding programs. In this research, the entire mitochondrial genome of A. officinalis was sequenced, annotated and assembled using a mixed Illumina and PacBio data. The garden asparagus circular mitochondrial genome measures 492,062 bp with a GC value of 45.9%. Thirty-six protein-coding genes, 17 tRNA and 6 rRNA genes were annotated, among which 8 protein-coding genes contained 16 introns. In addition, 254 SSRs with 10 complete tandem repeats and 293 non-tandem repeats were identified. It was found that the codons of edited sites located in the amino acids showed a leucine-formation trend, and RNA editing sites mainly caused the mutual transformation of amino acids with the same properties. Furthermore, 72 sequence fragments accounting for 20,240 bp, presentating 4.11% of the whole mitochondrial genome, were observed to migrate from chloroplast to mitochondrial genome of A. officinalis. The phylogenetic analysis showed that the closest genetic relationship between A. officinalis with onion (Allium cepa) inside the Liliaceae family. Our results demonstrated that high percentage of protein-coding genes had evolutionary conservative properties, with Ka/Ks values less than 1. Therefore, this study provides a high-quality garden asparagus mitochondrial genome, useful to promote better understanding of gene exchange between organelle genomes.